2016
DOI: 10.1016/j.comppsych.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Executive function in fibromyalgia: Comparing subjective and objective measures

Abstract: Patients with fibromyalgia showed executive dysfunction in subjective and objective measures, although most of this impairment was associated with mood disturbances. Exceptions to this general rule were observed in the impairment of working memory evidenced on the BRIEF-A scale and the inhibition impairment exhibited by the interference effect from the Stroop Test. The two types of measurement provide different yet complementary information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
73
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 60 publications
12
73
4
Order By: Relevance
“…Given the minimal improvement in pain intensity corresponding to a reduction of 3·5 mm on a 100 mm VAS (NS) and the statistically non‐significant improvements in mood (HAD‐D: 11·3–7·5, and HAD‐A: 8·6–7·8), we do not think it likely that reductions in pain or mood disturbances explained the improved SCWT performance in our patients. Furthermore, although depression and anxiety has been shown to influence cognitive function in FM, previous studies have shown that this is less pronounced regarding SCWT performance (Cherry et al ., ; Genlonch et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Given the minimal improvement in pain intensity corresponding to a reduction of 3·5 mm on a 100 mm VAS (NS) and the statistically non‐significant improvements in mood (HAD‐D: 11·3–7·5, and HAD‐A: 8·6–7·8), we do not think it likely that reductions in pain or mood disturbances explained the improved SCWT performance in our patients. Furthermore, although depression and anxiety has been shown to influence cognitive function in FM, previous studies have shown that this is less pronounced regarding SCWT performance (Cherry et al ., ; Genlonch et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The latter is supported by reports of poorer cognitive test performance in chronic pain patients compared to controls (Rathbone et al ., ). Self‐reported cognitive complaints, as well as poorer performance during cognitive testing compared to controls, have also been reported in patients with fibromyalgia (Rathbone et al ., ), although with inconsistent results and not always remaining after correction for depression and anxiety (Suhr, ; Genlonch et al ., ). However, impairments of executive functions, particularly selective attention, processing speed and inference inhibition as assessed by the Stroop colour word task (SCWT), have been documented in patients with fibromyalgia and remained even when adjusted for mood (Cherry et al ., ; Genlonch et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many chronic pain patients present impaired cognitive functioning 1, 2 , as indicated by poorer performance and slower reaction times in neuropsychological tasks 35 . These alterations occur more frequently in patients with generalized pain 6 such as fibromyalgia (FM), in which cognitive dysfunction has recently been recognized as one of its core symptoms 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that perceived dyscognition is related to objective cognitive impairments in memory, verbal fluency, attention/concentration and executive functioning (Kravitz & Katz, ; Park, Glass, Minear, & Crofford, ; Tesio et al., ). However, in addition to objective cognitive difficulties, other contributing factors, such as emotional distress, have demonstrated appreciable effects on fibrofog (Ambrose, Gracely, & Glass, ; Gelonch, Garolera, Valls, Rosselló, & Pifarré, ; Glass, Park, Minear, & Crofford, ). Core FM symptoms such as fatigue, unrefreshing sleep and mood alterations may contribute to fibrofog (Williams, Clauw, & Glass, ).…”
Section: Introductionmentioning
confidence: 99%